Pengaruh Pupuk Hayati Mikoriza dan Jarak Tanam Terhadap Pertumbuhan dan Produksi Tanaman Jagung Manis (Zea mays L. Saccharata Sturt) - Waruwu, Jhonisman; Sajar, Suryani; Luta, Devi Andriana (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The purpose of this study was to determine the effect of mycorrhizal biofertilizer and plant spacing on the growth and yield of sweet corn plants. This study was conducted from January 2025 to May 2025 in Sampe Cita Village, Kutalimbaru District, Deli Serdang Regency. The method used was a Randomized Block Design (RAK) consisting of 2 factors, 16 combinations and 3 replications, resulting in 48 experimental units. The first factor was the application of mycorrhizal biofertilizer consisting of 4 levels (M0: 0g/plant), (M1: 5g/plant), (M2: 10g/plant) and (M3: 15g/plant). The second factor was the plant spacing consisting of 4 treatments (J1: 70 x 15), (J2: 70 x 30), (J3: 70 x 45) and (J4: 70 x 60). The results of this study indicate that the application of mycorrhizal biofertilizer significantly affected plant height at 2 weeks after planting, ear length, fruit diameter, root weight, and root length. However, there were no significant differences in plant height at 4 and 6 weeks after planting, stem diameter, and fruit weight. Planting distance significantly affected stem diameter at 6 weeks after planting, fruit weight, ear length, fruit diameter, and root weight, while there were no significant differences in plant height, stem diameter at 2 and 4 weeks after planting, and root length